A systematic review of transparency in Lesson Study research: how do we report on the observation and reflection stages? - Kager, Klara; Kalinowski, Eva; Jurczok, Anne; Vock, Miriam (Frontiers in Education, 2024)
Lesson Study is a method of professional development for teachers that has gained traction in recent decades. However, publications routinely fail to describe crucial details of the implementation or to link the mechanisms that facilitate teachers learning in Lesson Study to theory. This makes it difficult to meaningfully synthesize and replicate research findings. Using a protocol based on Moravcsik's (2020) dimensions of transparency, this systematic review examines 129 articles on Lesson Study published between 2015 and 2020 to identify how transparent they were in their reporting of how teachers observed and reflected together. The findings indicate a lack of transparency across several dimensions of how the Lesson Study intervention is reported and highlight a current lack of theorization and coherence in the field. To address some of these issues, we propose a framing structure that empirical papers on Lesson Study should give critical attention to in order to ensure relevance and transferability.